Understanding and Predicting Northwest Atlantic Shelf Temperature Variability - Ke Chen (Geophysical Research Letters)
Abstract Coastal oceans, particularly the Northwest Atlantic continental shelf, are experiencing profound changes driven by global variability and local processes. These changes carry significant implications for marine ecosystems, fisheries, and coastal communities, underscoring the importance of understanding and predicting coastal variability. Koul et al. (2024), https://doi.org/10.1029/2024gl110946 contribute to this effort by utilizing a high‐resolution regional ocean model downscaled from a global prediction system to forecast a pause in the rapid warming of the Northwest Atlantic Shelf in the coming decade. This prediction, attributed to internal climate variability linked to a strengthening of Atlantic Meridional Overturning Circulation (AMOC) and a southward Gulf Stream shift, highlights the potential of regional models to improve predictive skill. While the study provides an important contribution, further research is needed to explore alternative modeling frameworks and improve understanding of key processes. Long‐term sustained observational programs remain critical for validating models and uncovering processes, enhancing prediction reliability.